2016
DOI: 10.1136/flgastro-2016-100705
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic vomiting syndrome: a case series and review of the literature

Abstract: Abbreviations:5 Design: Consecutive adult patients with CVS were identified during a 5-year period from January 2010 until December 2015. Medical records were reviewed retrospectively, and age and sex of the patient, symptoms, associated features, and response to treatment with amitriptyline were recorded.Setting: A luminal gastroenterology clinic at a teaching hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 65 publications
1
39
0
Order By: Relevance
“…47 In addition, we did not evaluate the subsequent management of these patients, an issue that has been highlighted in the literature as problematic for gastroenterologists, 13 although we have reported data from our center regarding the treatment of CVS previously. 48 In conclusion, the prevalence of CVS among adult patients in secondary care gastroenterology clinics in this study was 10.8%, but the diagnosis was considered in fewer than one-in-twenty individuals with typical symptoms, who had no structural explanation for these, and who likely had CVS. Education of gastroenterologists, and other physicians who are likely to encounter such patients, including those in primary care and the emergency department, is paramount in order to eliminate the diagnostic delay seen in adults, reduce the financial impact of the condition on both primary and secondary healthcare services, and to institute prompt and appropriate treatment in order to improve quality of life for these patients.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…47 In addition, we did not evaluate the subsequent management of these patients, an issue that has been highlighted in the literature as problematic for gastroenterologists, 13 although we have reported data from our center regarding the treatment of CVS previously. 48 In conclusion, the prevalence of CVS among adult patients in secondary care gastroenterology clinics in this study was 10.8%, but the diagnosis was considered in fewer than one-in-twenty individuals with typical symptoms, who had no structural explanation for these, and who likely had CVS. Education of gastroenterologists, and other physicians who are likely to encounter such patients, including those in primary care and the emergency department, is paramount in order to eliminate the diagnostic delay seen in adults, reduce the financial impact of the condition on both primary and secondary healthcare services, and to institute prompt and appropriate treatment in order to improve quality of life for these patients.…”
Section: Discussionmentioning
confidence: 65%
“…These include activation of the corticotrophin‐releasing factor signaling system, abnormal gastric motility, mitochondrial DNA mutations, and other genetic factors including variants in the RYR2 gene, which is involved in stress‐induced calcium channels in autonomic neurons, and polymorphisms in genes encoding endogenous cannabinoid and opioid receptors . In addition, we did not evaluate the subsequent management of these patients, an issue that has been highlighted in the literature as problematic for gastroenterologists, although we have reported data from our center regarding the treatment of CVS previously …”
Section: Discussionmentioning
confidence: 99%
“…The evidence on the use of TCAs in adults with CVS is based on open‐label and retrospective studies and two randomized controlled trials (RCTs) in children . There were fourteen studies that included 600 adult and pediatric patients . Across these studies, 413/600 (70%) of patients reported complete or partial improvement with a decrease in frequency, duration, or severity of CVS symptoms when treated with a TCA, most commonly amitriptyline.…”
Section: Prophylactic Medications In Cvsmentioning
confidence: 99%
“…• CVS has also been linked to autonomic dysfunction, mitochondrial disorders, hypothalamic-pituitary-adrenal activation and food allergy. 4 Children with CVS have been found to have augmented sympathetic tone and normal to low parasympathetic tone. In mitochondrial disorders, metabolic crisis with vomiting can be the presentation.…”
Section: Discussionmentioning
confidence: 99%